Macroscopic Portal Vein Thrombosis in HCC Patients - Akkiz, Hikmet; Carr, Brian I.; Kuran, Sedef; Karaogullarindan, Umit; Uskudar, Oguz; Tokmak, Salih; Kilic, Murat (Hindawi Ltd, 2018)
Macroscopic portal vein invasion (PVT) by hepatocellular carcinoma (HCC) in the liver is one of the most important negative prognostic factors for HCC patients. The characteristics of a large cohort of such patients were examined. We found that the percent of patients with PVT significantly increased with increasing maximum tumor diameter (MTD), from 13.7% with tumors of MTD <5cm to 56.4% with tumors of MTD >10cm. There were similar numbers of HCC patients with very large tumors with and without PVT. Thus, MTD alone was insufficient to explain the presence of PVT, as were high AFP levels, since less than 50% of high AFP patients had PVT. However, the percent of patients with PVT was also found to significantly increase with increasing blood alpha-fetoprotein (AFP) levels and tumormultifocality. A logistic regressionmodel that included these 3 factors together showed an odds ratio of 17.9 for the combination of MTD >5.0cm plus tumor multifocality plus elevated AFP, compared to low levels of these 3 parameters. The presence or absence of macroscopic PVT may therefore represent different HCC aggressiveness phenotypes, as judged by a significant increase in tumor multifocality and AFP levels in the PVT positive patients. Factors in addition to MTD and AFP must also contribute to PVT development.
Keywords: Gamma-Carboxy Prothrombin; Unresectable Hepatocellular-Carcinoma; Autologous Growth-Factor; Computed-Tomography; Prognostic-Factors; Alpha-Fetoprotein; Venous Invasion; Tumor; Survival; Ultrasound